Menggali Makna Keadilan Gender Berbasis Kearifan Lokal Lio-Sikka; Upaya Mengurangi Kekerasan Terhadap Perempuan Di Sikka - Abdullah Muis Kasim; Gisela Nuwa (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Universally, cultural strength can be a locus in building the character of the Indonesian nation as a global society. Cultural diversity can be a primary source of strength in developing the implicit meanings within that culture, especially regarding gender justice, which has recently been experiencing degradation. Through this cultural potential, it is hoped to address the polemic of violence against women and be used as a subsystem in handling gender justice issues for the Women's Empowerment and Child Protection Office. Culture, as a system of values born from the womb of local culture, should be used as a reference for stakeholders in resolving the complex issues of gender justice. This research aims to delve deeper into gender issues from the perspective of local wisdom of the Lio-Sikka ethnic group. Additionally, it seeks to explore and interpret the meaning of gender justice perceived by Lio-Sikka customs. The research method used is descriptive qualitative with an ethnographic approach developed by Spradley. The data collection techniques include observation, interviews, and documentation. The main data sources were taken from traditional elders, community leaders, and the head of the Women's Empowerment Office in Sikka Regency. The data analysis technique used the 12-step method developed by Spradley. The research results show: that first, the reconstruction of gender justice from the perspective of the local wisdom of the Lio-Sikka ethnic group reveals several points, namely in the context of patriarchal ideology, social construction, women and marriage rituals, women and legendary stories. Second, the Meaning of Gender Justice in Relation to Lio-Sikka Customs includes, Ine Weta, Ama Laki (Mother as Protector, Father as Leader), Lelu wolo, ina tana (Father as Mountain, Mother as Earth), Embo wawa wolo, nggika wawa tana (Women Climb Mountains, Men Descend Valleys), Lela laku, ine eme (Father as Leader, Mother as Housekeeper), Nggaa nggipa, naja nggipa.